Do the Poor Pay Twice? : Impact of Corruption in the Kyrgyz Republic - World Bank Group (World Bank, Washington, DC, 2016)
This study examines household perceptions and experiences with corruption in the Kyrgyz Republic. The aims of the study are two-fold: first, to assess the level of administrative corruption in public service agencies, and second, to assess the impact of corruption on different income groups. This Poverty and Social Impact Analysis (PSIA) included a nationally-representative survey covering over 1,000 households in all regions of the country and focus groups with citizens, civil society organization (CSO) representatives, media and students.